53rd Electronic Components and Technology Conference, 2003. Proceedings.
DOI: 10.1109/ectc.2003.1216544
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of flip-chip packaging challenges on copper low-k interconnects

Abstract: As industry trends drive increased integration and speed, Cuilow-k structures are the desired choice for advanced IC circuits. A simulation methodology has been developed to study the flip-chip packaging effect on the Cullow-k structures. Multi-level submodeling techniques have heen used to bridge the scale difference between the flip-chip packages and the metalidielectric stacks. Interface fracture mechanics-based approach is used to determine the crack driving force at each interface. The impact of the die-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 4 publications
(5 reference statements)
1
22
0
Order By: Relevance
“…2(b). This interconnection is produced by an extra build-up process step that adds bumps to all the pads on the entire wafer [21]. To integrate STOs with ICs by using flip-chip, STOs are placed on coplanar waveguides so that they can be connected to the bumps on ICs.…”
Section: Integration Considerationsmentioning
confidence: 99%
“…2(b). This interconnection is produced by an extra build-up process step that adds bumps to all the pads on the entire wafer [21]. To integrate STOs with ICs by using flip-chip, STOs are placed on coplanar waveguides so that they can be connected to the bumps on ICs.…”
Section: Integration Considerationsmentioning
confidence: 99%
“…Eventually, high-filler compounds with CTE values better matching to silicon gave sufficient results. For flip-chip packages, a solution was found in changing the metal layout in the IC layers [22,23]. For instance, the placement of active circuitry in the region beneath bondpads represents an effective method for not sacrificing either assembly or package reliability.…”
Section: Mouldmentioning
confidence: 99%
“…FE techniques are widely used to predict the deformations and stresses and their evolution during IC processes, packaging manufacturing processes, and/or product testing [4,5,8,[17][18][19][20][21][22][23][24][25][26]. Modelling techniques such as contact elements, global-local, sub-structuring, element birth and death, fracture mechanics and material models such as visco-elasticity, plasticity and creep are rapidly developed to predict the stress and strain state in the electronic Fig.…”
Section: Facing the Future: Cmos065 And Beyondmentioning
confidence: 99%
“…Mercado et al found that the crack driving force at the critical interface increases with increasing number of interconnect layers [3]. They showed that the crack driving force for low-k structures is higher than that for SiO 2 interconnects.…”
Section: Introductionmentioning
confidence: 97%